Sistem Pakar Menggunakan Metode Certainty Factor dalam Akurasi Identifikasi Penyakit pada Paru - Siska, Ayu Prima; Yunus, Yuhandri; Sumijan, Sumijan (Jurnal Sistim Informasi dan Teknologi, 2021)
Lungs are a very importand part of the human organ, which functions as a place for oxygen exchange. This organ that is located under the ribs has a very heavy task, as well as the pollution of the air we breathe everyday which will cause various diseases in the lungs. Lung disease is a disease that is common to everyone, and there are still many who are less concemed with lung healty, so that is causes many indications of lung diseas. Expert system is a system that uses human knowledge recorded in a computer to solve a problem. The purpose og this study was to datermine the accuracy of disease identification in the lungs using the Certainty Factor method. The date obtained is datae about the symptoms that prove wherher a person has lung disease or not and conduct an analysis of the date, so that later conclusions can be abtained from the facts found using an expert system of the Certianty Factor method. The date obtained is date about the sympyoms thet prove whethera person has lung as a problem solving metric which is a parameter value to show the amount of trust. The result of the research from an expert system on pulmonary disease with pulmonary tuberkolosis (TBC) with a certainty level og 68%. Expert system on lung disease using the Certainty Factor method can make it easien for sufferes to know and handle prevention and handling.